Identification and assessment - Mastropieri, Margo A. 1951-; Scruggs, Thomas E. 1948- (JAI Press, 2003)
Identification and assessment of learning and behavioural disabilities have long been issues of great concern, and have become increasingly important in recent years. Identification and assessment issues determine how students are characterized as having disabilities, provide implications for treatment, and provide evidence for the success or failure of interventions. In this volume, several topics of relevance to the issue of identification and assessment of learning and behavioural disabilities are discussed by leading scholars, in reviews of recent relevant research, policy analyses, and new investigations with original data. This book is intended for interested professionals and practitioners; researchers in learning and behavioural disabilities; and graduate students in psychology, education, and special education.